It’s About Time: Initial Findings From a Feasibility Study of a Time-Study Tool for School Social Workers in Michigan - Michael S. Kelly; Steven Whitmore (International Journal of School Social Work, 2019)
Starting in late Summer of 2015, the two authors began collaborating on the pilot testing of a school social work (SSW) time-study tool with a sample of SSW in suburban Detroit (n=9). This article details the path towards the development of the time-study tool, drawing from the extant literature on workload and caseload issues in related special education fields, and resulting in the time-study tool that was first piloted with SSW in 2015-2016. Initial data from year one of the two-year 2015-2017 pilot project is shared in this article, along with qualitative data based on interviews with the SSW in the project, as well as reflections by the two authors on the implications of the work in this first pilot year. This article describes in detail the background for this project, the procedures followed, the initial results after year one, and how these findings informed plans for year two.
Keywords: school social work; workload; caseload; evidence-based practice; special education; IEP